The Impact of Strategic Planning on Aligning Higher Education Outcomes with The Labor Market Needs in The Sultanate of Oman - Abdullah Said Obaid Alshaaibi; Salah Mohamad Zaki Ibrahim; Khairunneezam bin Mohd Noor; Ahmed Abdul Malik (WorldConferences.net, 2024)
E-JOURNAL OF THE INTEGRATION OF KNOWLEDGE 2020 (8th EDITION) (e-ISSN: 2289-5973).